Ways to Increase Employment in the Service Sector - ogli, Usmonov Murodbek Dusmurot (Journal of Multidisciplinary Academic and Practice Studies, 2026)
Purpose: This study investigates the structural, technological, and institutional factors affecting employment growth in Nigeria's service sector from 2010 to 2023. It examines how structural transformation, innovation, and institutional frameworks influence service-sector expansion using global employment data from the World Bank and other sources. Research Methodology: A multilevel analytical framework is applied, focusing on structural changes, innovation dynamics, and institutional influences based on global employment data. Results: By 2023, service-sector employment had grown to over 50% of the total employment, while agricultural employment declined and industrial employment remained stable. Service-sector growth does not automatically lead to inclusive or high-quality employment. Digitalization and innovation have varying effects, with knowledge-intensive services creating higher-skilled jobs, while automation risks displacing routine labor. Institutional quality plays a key role in determining whether service-sector growth follows a high-road path (productivity and decent work) or a low-road path (informality and precarious employment). Conclusions: This study emphasizes the importance of policies ensuring that service-sector growth results in inclusive, sustainable, and high-quality employment. Institutional quality is critical in shaping these outcomes. Limitations: This study is limited by its reliance on secondary data, which may not fully capture local or nuanced employment trends. Contributions: This study provides a multilevel framework integrating structural, technological, and institutional factors, with policy recommendations for middle-income economies seeking sustainable service-sector development.